The relationship between hip muscle strength and dynamic knee valgus in asymptomatic females: A systematic review. (May 2019) - Dix, Jack; Marsh, Stephanie; Dingenen, Bart; Malliaras, Peter
Abstract: Objective: To systematically review literature investigating the relationship between hip muscle strength and dynamic lower extremity valgus during movement tasks in asymptomatic females. Methods: Four databases (CINAHL, SPORTDiscus, Embase and Ovid MEDLINE) were searched in February 2017. Studies investigating the relationship between hip muscle strength and dynamic knee or lower extremity valgus during movement tasks among asymptomatic females over 18 years old were included. Meta-analyses were performed where two or more studies used similar tasks. Results: Five studies reported no relationship between hip strength and dynamic lower extremity valgus. Greater peak lower extremity valgus was associated with reduced hip strength in eight studies, and greater hip strength in three studies. In the meta-analysis, a relationship between weaker hip strength and greater dynamic lower extremity valgus was found for ballistic single leg landing, but not double leg landing or single leg squat tasks. Conclusions: Although the relationship between hip strength and dynamic lower extremity valgus is conflicting, meta-analysis revealed lower extremity dynamic valgus was consistently associated with hip strength in single leg ballistic tasks, but not double leg ballistic or single leg squat tasks. The relationship between hip strength and dynamic lower extremity valgus may be conditional to task demand. Highlights: Evidence on a link between hip strength and dynamic knee valgus is conflicting. Strength testing protocols and movement tasks assessed vary. Study designs using single leg, ballistic landings more likely to show correlation. The relationship between hip strength and dynamic knee valgus may be task dependent.